أنواع وقياس المعنى - Bagas Mukti Nasrowi (Universitas Yudharta Pasuruan, 2019)
Although the scholars differ in the enumeration of the types of meaning, we see that the five types of the most important are: the basic meaning, the additional meaning, the stylistic meaning, the psychological meaning and the meaning of inspiration. Linguists and psychologists used the measure of meaning to achieve several purposes: measuring the basic meaning of contrasting words, measuring differences and differences in internal psychological meanings in individuals, measuring physiological responses, and measuring the meanings of events. It is also a measure of meaning: participation is what united its image and its meaning is different. Contradiction is the signification of the word on two equally opposites. The synonym is the single word that indicates one thing as one.